Καὶ ἄϕες ἡμῖν τὰ ὀφειλήματα ἡμῶν … the Lord"s Prayer (Mt 6:12, Lk 11:4) and dispute resolution in the African church: The Ewe-Ghanaian context and perspective - Sakitey, Daniel (HTS teologiese studies, 2021)
This article examines the fifth petition of the Lord’s Prayer in Matthew in the light of Ewe-Ghanaian conflict management model. Theoretically, the article employs a combination of the historical-critical and indigenous mother tongue biblical hermeneutical approaches to explore the implication of the petition for Ewe-Ghanaian Christian spirituality. The main theme of the petition in both Matthew and Luke’s renditions of the petition is forgiveness, which employs a divine-human and human–human formula, with the human–human serving as a form of collateral for the divine-human. Whereas Matthew’s petition carries an eschatological motif that of Luke is viewed in a non-eschatological sense. The article discusses the various theological and hermeneutical positions of the text and dialogically engages the world of the text with the Ewe-Ghanaian conflict resolution model with the view of finding points of continuity and discontinuity, if any. The article argues that divine-human and human–human forgiveness model, and the eschatological and non-eschatological interpretations suggested in both Matthew and Luke, respectively, does not resonate with Ewe-Ghanaian worldview, which perceives conflict from a demonological point of view. Any conflict resolution model that does not take the demonological dimension into consideration cannot be trusted to deliver justice in conflict situations. Thus, the task of the 21st century Ewe-Ghanaian church is to design an alternative dispute resolution (ADR) that resonates with the Ewe-Ghanaian life and thought pattern and is able to deliver justice.Contribution: Matthew’s rendition of the fifth petition of the Lord’s Prayer from the perspective of Ewe-Ghanaian conflict resolution model is the focus of this article. The article forms part of the researcher’s contribution to the academic knowledge on the Lord’s Prayer and inspires the use of Mother Tongue Biblical hermeneutics in the development of theological materials for the Ewe-Ghanaian Christian communities in Ghana and Togo.